DISTRIBUTION OF CHLOROPHYLL-a CONCENTRATION IN WEST SUMATERA CONNECTED BY THE RESULTS OF TUNA’S ARREST - Destuanti, Nia; YulikaSari, T. Ersti; Jhonnerie, Romie (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Chlorophyll-a is one of indicator’s level in fertility waters that be found in phytoplankton. The distributed of Chlorophyll-a concentration can be indication that so many fish in the waters. One of potential fishing in Hindia’s ocean, west Sumatera section is Thunnus obesus and Thunnus albacares to identifed the content of Chlorophyll-a can be used aqua MODIS satelite. The goals of this research is to know the distribution of Chlorophyll-a concentration and the effort arrest in spasial and temporal (montly, seasonal, yearly) and then to knew the correlation between effort arrested with Chlorophyll-a data. This research used density’s analysis by used QGIS. The correlation between Chlorophyll-a with effort arrested (CPUE) that can be found from analysis of coefficient correlation for montly periods by the highestvalue r: 0,72 in May with the results both of variabel had powerful correlation and the lowest value r: 0,02 in December with the results both of variabel had weak correlation. The highest of coefficient correlation in seasonal period with r: 0,47 in trantition seasonal as the results both of variabel had medium correlation and the lowest value r: 0,04 in west season as the results both of variabel had weak correlation.Keywords: Hindia’s Ocean, bigeye tuna (Thunnus obesus), yellowfin tuna (Thunnus albacares), chlorophyll-a, Aqua MODIS